Quilombolas women: protagonism, identity, territory and territoriality of black women in São Miguel do Guamá/Pará - Ana Célia Barbosa Guedes; Mayany Soares Salgado (Revista Eletrônica História em Reflexão, 2020)
This article analyzes the protagonism and identity of black women, in Santa Rita de Barreira quilombo as a territory and territoriality of blackness. The quilombo is located in the municipality of São Miguel do Guamá, on the State of Pará. As methodological procedures, we use bibliographic research and oral history. In this sense, semi-structured interviews were conducted for data collection and participant observation.Therefore, we observein this territory, black women are protagonists of their own history and through mobilization and political organization in association or in a group of women they fight for public policies to ensure theirsubsistence and that of their social group. Besides that, they also many tasks such as domestic, female farmers and others.